Social dimensions of volcanic hazards, risk and emergency response procedures in southern Iceland - Bird, Deanne Katherine (2010)
The Katla volcano in southern Iceland is one the most hazardous in the country. Frequent, destructive eruptions producing catastrophic jökulhlaup (glacial outburst floods), tephra fall and lightning hazards pose a serious risk to many local communities. Extensive geological and geophysical research details the current state of Katla and provides insights into past eruptive episodes but only one study, conducted with residents from two communities in 2004, had assessed Katla with respect to the local population. In order to develop successful risk mitigation strategies however, emergency management agencies must consider the hazard in conjunction with the varying factors affecting the society at risk. As a result, this research explores some of the social dimensions of hazard, risk and emergency response procedures in relation to Katla. The aim of the research is to provide a social framework for disaster risk reduction by offering an in-depth social assessment to complement the physical. Using mixed methods research, the study incorporates field observations during evacuation exercises, semi-structured interviews with emergency management officials and residents, and structured questionnaire interviews with residents, tourists and tourism employees. The research shows that each stakeholder group is inherently different and volcanic risk mitigation strategies need to be structured accordingly. Recent efforts which culminated in full-scale evacuation exercises in 2006 did not take this into consideration. On a practical level, these exercises indicated that most residents would respond positively to evacuation orders. At a conceptual level however, this research identified many contextual issues, (e.g. knowledge and perception of hazard and risk, level of trust) which affect people’s ability to adopt the recommended protective action. In rural communities, emergency management agencies need to consider local knowledge, livelihood connections and attachment to place in order to develop effective mitigation ...